Lontas: The aesthetic concept of mortar music of farmer community in Turi Village, Indonesia - Primamona, Dea Lunny; Sunarto, Bambang (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2025)
This research is focused on the phenomena of an aesthetic impression in kothékan lesung performed by a farmer community in Turi Village, Magetan District, Indonesia. This research aims to understand the kothékan lesung as an art system and understand the idiom lontas expressed verbally in their mortar music performance. This research uses an ethnomusicology approach which includes fieldwork and deskwork. The research is sequentially conducted with observation, interviews, recordings, measurements, and studying literature and documents. This article uses Sedyawati’s concept about the art system and Sethares’s concept about the science of sound to analysis data. The result shows that: (1) kothékan lesung has elements of its art system including: (a) community aesthetics sources; (b) artists (panjak); (c) creation and enjoyment of art; and (d) art objects (music instrument mortar and pestle) and artworks (gendings); and (2) lontas can be understood as the aesthetic impression from the artist to enjoy artworks. The artwork contains quality of sound which has the following criteria, such as: (a) loud volume and rapid intensity; (b) precise and clear timbre; (c) solid form; and (d) raise the subjective pleasant. Based on the mortar sound spectrum analysis, the phenomena of lontas can be easily understood as a perceptual rather than a physical phenomenon. However, the presence of lontas is very important in the kothékan lesung in Turi community. Lontas is the highest standard in panjak’s embodiment which can only be felt when they play together. It can be used to transmit musical knowledge orally among the community.